Behavioral and Neuropathological Changes After Toxoplasma gondii Ocular Conjunctival Infection in BALB/c Mice - Soares, Gabrielly Lisboa da Silva; Leão, Ellen Rose Leandro Ponce de; Freitas, Sinara Franco; Alves, Raissa Maria Carvalho; Tavares, Naiana de Paula; Costa, Maria Vitória Nascimento; Menezes, Gabriel Castro de; Oliveira, Jhonnathan Henrique Palheta de; Guerreiro, Luma Cristina Ferreira; Assis, Alexa Camila Lopes de; Araújo, Sanderson Corrêa; Franco, Felipe Tuji de Castro; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Ocular infection with Toxoplasma gondii causes toxoplasmosis in mice. However, following ocular infection with tachyzoites, the cause of the accompanying progressive changes in hippocampal-dependent tasks, and their relationship with the morphology and number of microglia, is less well understood. Here, in 6-month-old, female BALB/c mice, 5 μl of a suspension containing 48.5 × 106 tachyzoites/ml was introduced into the conjunctival sac; control received an equal volume of saline. Before and after instillation, all mice were subject to an olfactory discrimination (OD) test, using predator (cat) feces, and to an open-field (OF) task. After the behavioral tests, the animals were culled at either 22 or 44 days post-instillation (dpi), and the brains and retinas were dissected and processed for immunohistochemistry. The total number of Iba-1-immunolabeled microglia in the molecular layer of the dentate gyrus was estimated, and three-dimensional reconstructions of the cells were evaluated. Immobility was increased in the infected group at 12, 22, and 43 dpi, but the greatest immobility was observed at 22 dpi and was associated with reduced line crossing in the OF and distance traveled. In the OD test, infected animals spent more time in the compartment with feline fecal material at 14 and at 43 dpi. No OD changes were observed in the control group. The number of microglia was increased at 22 dpi but returned to control levels by 44 dpi. These changes were associated with the differentiation of T. gondii tachyzoites into bradyzoite-enclosed cysts within the brain and retina. Thus, infection of mice with T. gondii alters exploratory behavior, gives rise to a loss in predator’s odor avoidance from 2 weeks after infection, increased microglia number, and altered their morphology in the molecular layer of the dentate gyrus.